Industrial contribution to the air quality of one mid-sized portuguese city - Silva, Lígia Torres (2010)
Urban air pollution became one of the main factors of degradation of the quality of life in cities. This problem tends to worsen due to the unbalanced development of urban spaces and the incompatibilities of uses. In urban environment the typical anthropogenic sources are mainly the road traffic and, when existing, the industrial activity. The present work was performed to attain the following objectives: to quantify the atmospheric emissions from the major industrial sources located in the city and its vicinity and to evaluate the influence of these industrial sources to the air quality of the city. A range of numerical models were used to produce the concentration maps: the ADMS-Urban model for the pollutants dispersion; the Hills model to calculate air flow and turbulence over complex terrain and the European Pollutant Emission Register to estimate the emission factors.